Survival outcomes of management in metastatic gastric adenocarcinoma patients - Huang-Ming Hu (Nature Portfolio, 2021)
Abstract Chemotherapy is generally considered as the main treatment for metastatic gastric adenocarcinoma. The role of gastrectomy for metastatic gastric cancer without obvious symptoms is controversial. The objective of this study is to investigate survival outcomes of treatment modalities using a real-world data setting. A retrospective cohort study was designed using the Taiwan Cancer Registry database. We identified the treatment modalities and used Kaplan–Meier estimates and Cox regressions to compare patient survival outcomes. From 2008 to 2015, 5599 gastric adenocarcinoma patients were diagnosed with metastatic disease (M1). The median overall survival (OS) of patients with surgery plus chemotherapy had the longest survival of 14.2 months. The median OS of the patients who received chemotherapy alone or surgery alone was 7.0 and 3.9, respectively. Age at diagnosis, year of diagnosis, tumor grade, and treatment modalities are prognostic factors for survival. The hazard ratios for patients who received surgery plus chemotherapy, surgery alone, and supportive care were 0.47 (95% CI 0.44–0.51), 1.22 (95% CI 1.1–1.36), and 3.23 (95% CI 3.01–3.46), respectively, by multivariable Cox regression analysis when using chemotherapy alone as a referent. Chemotherapy plus surgery may have a survival benefit for some selected gastric adenocarcinoma patients with metastatic disease.